Urban drainage of the large cities in the Hydrographic Basins of the Piracicaba, Capivari and Jundiaí Rivers - Ferreira, Denise Helena Lombardo; Guedes, Walef Pena; Fruehauf, Amanda Lombardo; Lombardo, Magda Adelaide; Sugahara, Cibele Roberta (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
The intense transformation of the landscape has been occurring dynamically in the Hydrographic Basins of the Capivari, Piracicaba and Jundiaí Rivers. This work aims to perform a survey of indicators related to the drainage of some municipalities inserted in these watersheds in order to point out the relationship of these indicators among the selected municipalities. The methodology used was a descriptive approach and case study. The indicators were selected and collected in the Stormwater section of the Historical Series of the National Sanitation Information System for the municipalities of Campinas, Indaiatuba, Jundiaí, Limeira, Piracicaba and Sumaré, years 2017 to 2020. The results suggest that the municipality of Campinas slightly outperforms the others. Moreover, the analysis of the indicators referring to urban drainage in the analyzed period revealed the need for reliable data to be later used in appropriate decision-making.